Dissecting impact of regional identity and oncogenic role of human-specific NOTCH2NL in an hESC model of H3.3G34R mutant glioma - Funato, Kosuke (Cell Stem Cell, 2021)
H3.3G34R-mutant gliomas are lethal tumors of the cerebral hemispheres, with unknown mechanisms of regional specificity and tumorigenicity. We developed a human embryonic stem cell-based model of H3.3G34R-mutant glioma that recapitulates the key features of the tumors, with cell type-specificity to forebrain interneuronal progenitors but not hindbrain precursors. We show that H3.3G34R, ATRX and TP53 mutations cooperatively impact alternative RNA splicing events, particularly suppression of intron retention. This leads to increased expression of components of the Notch pathway, notably NOTCH2NL, a human-specific gene family. We also uncover a parallel mechanism of enhanced NOTCH2NL expression via genomic amplification of its locus in some H3.3G34R-mutant tumors. These findings demonstrate a novel mechanism whereby evolutionary pathways that lead to larger brain size in humans are co-opted to drive tumor growth.